2017
DOI: 10.1111/jog.13266
|View full text |Cite
|
Sign up to set email alerts
|

Increased ipsilateral uterine artery vascular resistance in women with ovarian endometrioma

Abstract: The UtA-vascular resistance might be higher on the ipsilateral side of the endometrioma than on the contralateral unaffected side, indicating a risk of subclinical atherosclerosis in women with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Among the full-text articles reviewed, 27 were excluded for various reasons (one German article, one letter to the editor, two commentaries, nine review articles, seven abstracts-only, three case reports, four doubling of the data). Ultimately, 12 studies were deemed eligible and included in qualitative synthesis: this included two prospective cohort studies (Mu et al, 2016(Mu et al, , 2017, four studies reporting lipid profile (Crook et al, 1997;Hopeman et al, 2015;Melo et al, 2010;Verit et al, 2008) and six studies (three cross-sectional, three case-control) that compared lipid profiles as well as other markers of endothelial dysfunction and atherosclerosis (Kinugasa et al, 2011;Pretta et al, 2007;Santoro et al, 2012Santoro et al, , 2014Tani et al, 2015;Waratani et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the full-text articles reviewed, 27 were excluded for various reasons (one German article, one letter to the editor, two commentaries, nine review articles, seven abstracts-only, three case reports, four doubling of the data). Ultimately, 12 studies were deemed eligible and included in qualitative synthesis: this included two prospective cohort studies (Mu et al, 2016(Mu et al, , 2017, four studies reporting lipid profile (Crook et al, 1997;Hopeman et al, 2015;Melo et al, 2010;Verit et al, 2008) and six studies (three cross-sectional, three case-control) that compared lipid profiles as well as other markers of endothelial dysfunction and atherosclerosis (Kinugasa et al, 2011;Pretta et al, 2007;Santoro et al, 2012Santoro et al, , 2014Tani et al, 2015;Waratani et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a case-control study using baPWV as an instrumental measure of endothelial dysfunction found significantly higher values in women with endometriosis (1187.5 ± 142.5 versus 1063.1 ± 12.3, P < 0.05), which reflects an increased ASCVD risk (Tani et al, 2015). A recent study also reported increased UtA RI on the ipsilateral side in patients with an endometrioma compared with those without (Waratani et al, 2017). In addition, the diameter of the ascending branch of the UtA was significantly greater on the side of the endometrioma than the contralateral side among women with endometriosis and ipsilateral side among normal controls (3.91 ± 0.15 mm versus 3.50 ± 0.23 mm versus 3.42 ± 0.15 mm, P < 0.01, respectively).…”
Section: Atherosclerosis and Serum Markers Of Ascvd Associated With Endometriosismentioning
confidence: 96%
See 1 more Smart Citation